Pengelolaan Evaluasi Aspek Sosial dalam Pembelajaran Matematika Kurikulum 2013 di Sekolah Menengah Pertama - Emi Fitriyani; Sutama Sutama; Sabar Narimo (Manajemen Pendidikan, 2016)
The   purpose   of   this   research   is:   to   described   the   management   of   learning mathemathics  evaluation  on social aspecs which is commited  by teacher to the student of Junior  High School  in Sirampog,  District  Brebes.  This research  is research  development (Research  and Development)  which originates  from certain problems  and continued  with Quasi   Experimental,   that   is   about   the   management   of   of   learning   mathemathics curriculum  2013 evaluation,  and measurement  of effectiveness  by comparing the result of assesment   before   developed   with   already   developed   by  using   kualitatif   deskription. According to the result of research and discussion that has been done, then researcher can conclude  as following  statement:  Management  of learning  mathemathics  evaluation  with curriculum  2013 in Junior  High School  in Sirampog  District  Brebes,  has been make an assesment  optimally,  but in the attitude  competence  especially  in self and inter student assesment were not maximized  because many teacher give a general declaration  not focus on mathemathics,  and also this evaluation is only implemented  in early curriculum  2013. In the recent time, many teacher are not evaluate and assesment instrument is not change. However, evaluation must be develop and consistent, in order to become better.